Mandated IOL Removal for Cure of Recurrent Enterococcus Faecalis Endophthalmitis: A Case Report. (17th November 2021) - Liu, Guangsen; Li, Yue; Gao, Lei
ABSTRACT: With modern technology and peri-op antibiotic use, postoperative endophthalmitis is uncommon to modern cataract surgery, and its recurrence even more unusual. Enterococcal faecalis endophthalmitis is an acute type of endophthalmitis that is not only rare, but can be recurrent, and has a poor functional prognosis [1]. Since the disease is refractory to conventional therapy, this paper details our experience with treating the disease given the current lack of standard care both medically and surgically.